AB0758 The Relationships between Bone Mineral Density and Radiographic Features of Hand or Knee Osteoarthritis in Older Adults: Data from The Dong-Gu Study. (15th July 2016) - Lee, K.-E.; Wen, L.; Yim, Y.-R.; Kim, J.-E.; Lee, J.-W.; Park, D.-J.; Lee, S.-S.
Abstract : Objectives: The relationship between osteoarthritis (OA) and osteoporosis has exhibited contradictory features over the past four decades. The aim of this study was to evaluate this relationship using separate analysis of the radiographic features of OA whether various radiographic features of OA were associated differently with bone mineral density (BMD) in the Korean elderly. Methods: Data were derived from the Dong-gu cohort; 2, 354 subjects were enrolled in the present cross-sectional study. Baseline characteristics, the BMDs of the lumbar spine and femoral neck which was measured by DXA, and X-rays of knees and hands, were collected. A semi-quantitative grading system was used to estimate the severities of individual radiographic features. We adjusted for confounders using multiple linear regression modeling to analyze the relationships. Results: After adjustment for confounders, hand and knee OA total scores were negatively associated with the BMDs of the lumbar spine and femoral neck, except for the total knee OA score and lumbar spine BMD. In detail, hand osteophytes and sclerosis exhibited positive relationships with the BMDs of the lumbar spine and femoral neck, except for hand osteophytes and femoral neck BMD. On the contrary, however, knee joint space narrowing (JSN), hand JSN, and hand subchondral cysts were negatively associated with the BMD of the lumbar spine and femoral neck. Knee JSN and hand subchondral cysts exerted the greatest effects on BMD. Conclusions: Separate analysis of the radiographic features of OA better reveals associations of OA with the BMD of the lumbar spine and femoral neck. Disclosure of Interest: None declared